The Effectiveness of Experiential Learning Models Based on Local Culture in Shaping Pancasila Character in Early Childhood - Martuty, Arie; Gani, Hamsu Abdul; Muharram, Muharram (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2024)
Character education is a crucial aspect in shaping a generation that is integrated, united, and appreciates the nation's noble values. However, technological developments and social phenomena in Indonesia indicate a decline in character among the younger generation, especially in early childhood education (PAUD) settings. This study aims to develop an experiential learning-based learning model rooted in local culture to shape the character of Pancasila in early childhood. The research methodology used is research and development (R&D) with quantitative and qualitative approaches. The model trial was conducted at TK RAMA, Group B, using observation techniques and paired sample t-tests to measure changes in children's character. The results show that the application of the ARIE model has a significant impact on improving the development of Pancasila character in the students, with an average N Gain score of 0.8, indicating the effectiveness of the model in character building. This learning model successfully created a learning environment that supports the development of values such as cooperation, independence, critical thinking, and creativity in children. Based on these findings, the experiential learning model based on local culture can be a solution for implementing Pancasila character education in PAUD and contribute to forming a generation with strong integrity and a high sense of nationalism.